Understanding the determinants of adoption of enterprise resource planning (ERP) technology within the agrifood context - Haberli Júnior, Caetano (2017)
The object of this study is to investigate the determinants of adoption of Enterprise Resource Planning (ERP) technology in agricultural farms located in the Central-West region of Brazil. The data was collected from 200 in-depth interviews with soy, corn and cotton farmers from the State of Mato Grosso, Brazil. Structural Equations methodology was used to analyze the data and hypothesis. The conceptual model was proposed by combining Diffusion of Innovations and Technology-Organization-Environment theories. The results provide information to agribusiness owners, managers and administrators to promote and incentivize the use of ERP. Politicians and farmers can evaluate each scenario and support their political and administrative decisions through the evaluation of socioeconomic and environmental performances of agricultural exploration as a result of technological innovation. This leads to a need for an analytical tool for the farmers, with the objective of supporting the adoption of optimized ERP for agri-food activities.